2012
DOI: 10.1214/12-aos1043
|View full text |Cite
|
Sign up to set email alerts
|

Nonparametric regression for locally stationary time series

Abstract: In this paper, we study nonparametric models allowing for locally stationary regressors and a regression function that changes smoothly over time. These models are a natural extension of time series models with time-varying coefficients. We introduce a kernel-based method to estimate the time-varying regression function and provide asymptotic theory for our estimates. Moreover, we show that the main conditions of the theory are satisfied for a large class of nonlinear autoregressive processes with a time-varyi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
101
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 141 publications
(106 citation statements)
references
References 24 publications
2
101
0
3
Order By: Relevance
“…Then from (iii) in the proof of Theorem 4.2 in Vogt (2012), we can show that B j (τ, x) converges in probability to B j,τ,x .…”
Section: A1 the Npr Modelmentioning
confidence: 87%
See 2 more Smart Citations
“…Then from (iii) in the proof of Theorem 4.2 in Vogt (2012), we can show that B j (τ, x) converges in probability to B j,τ,x .…”
Section: A1 the Npr Modelmentioning
confidence: 87%
“…Typically, y t is (logarithmic) stock returns, but we may also be interested in predicting prices. A locally stationary process is defined as follows (see Vogt (2012)). …”
Section: The Npr Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…errors (even assumed to be Gaussian in some cases) [see Müller (1992) for an early reference and Mallik et al (2011) and Mallik et al (2013) for more recent references]. Recently Vogt and Dette (2015) proposed a generalized CUSUM approach to detect gradual changes in model (2.1) using a different concept of local stationarity [see Vogt (2012)]. …”
Section: Piecewise Locally Stationary Processesmentioning
confidence: 99%
“…Using a simplified version of the proof for Theorem 4.1 in Vogt (2012) or alternatively applying Theorem 1 of Kristensen (2009), it can be shown that sup u∈[0,1] |g V (u)| = O p ( log T /T h). In addition, straightforward calculations yield that sup u∈[0,1] |g B (u)| ≤ Ch 2 for some sufficiently large constant C. This completes the proof of the uniform convergence result.…”
Section: Proof Of Theoremmentioning
confidence: 99%